The Lost - Patterson, James, 1947-; Raymond, Emily, 1972- (Patterson, James, 1947- Witch & wizard novels, 2014)
"Magical teen siblings Whit and Wisty Allgood struggle against a mounting public opposition to magic and a brutal crime wave led by a powerful wizard intent on ruling the City"--